Transition metal elements-doped SnO2 for ultrasensitive and rapid ppb-level formaldehyde sensing. Issue 2 (February 2023) - Han, Zejun; Tang, Yunxiang; Lu, Guixia; Qi, Yuan; Wu, Hao; Yang, Zhengyi; Han, Hecheng; Zhang, Xue; Wu, Lili; Wang, Zhou; Liu, Jiurong; Wang, Fenglong
Abstract: Pristine SnO2, Fe-doped SnO2 and Ni-doped SnO2 were synthesized using facile hydrothermal method. Analysis based on XRD, TEM and UV–Vis DRS measurements demonstrated the successful insertion of Fe and Ni dopants into SnO2 crystal. Formaldehyde-detection measurements revealed that transition metal-doped SnO2 exhibited improved formaldehyde-sensing properties compared with that of pristine SnO2 . When the amount of incorporated dopant (Fe or Ni) was 4 at.%, the most effective enhancement on sensing performance of SnO2 was obtained. At 160 °C, the 4 at.% Fe–SnO2 and 4 at.% Ni–SnO2 exhibited higher response values of 7.52 and 4.37 with exposure to low-concentration formaldehyde, respectively, which were 2.4 and 1.4 times higher than that of pristine SnO2 . The change of electronic structure and crystal structure as well as catalytic effect of transition metals are chiefly responsible for the enhanced sensing properties. Graphical abstract: This work constructed transition metal elements-doped SnO2 with optimized electronic structure and crystal structure, which significantly enhanced the sensing performance towards low-concentration formaldehyde. Image 1